PERANCANGAN SPACE MAKERDI PERPUSTAKAAN UNIVERSITAS SURABAYA SEBAGAI UPAYA PENINGKATAN FUNGSI FASILITAS DALAM PEMBELAJARAN DAN PENELITIAN - Maudy Margaretha; Elieser Tarigan; Wyna Herdiana (Perpustakaan Universitas Surabaya, 2018)
Abstract - Library as an academic support should have some complete, organize, and fuctional components than can support in learning, research, and community service. Makerspace will be added to Surabaya University library. Makerspace is a place for sharing tools, knowledge, and ideas. Library will not be a silent space anymore, but an open place to expression and develop creativity. The purpose of this research is to design makerspace table in Surabaya University for improving the facilities by using qualitative method through a book or internet and quantitative method by interview. The result of this research is a makerspace table with modern-futurictic concept and have many features to simplify the user, such a lighting, cutting mat, dustbin, stationery space, book shelves.